Les quantifieurs nominaux d’origine météorologique ou hydrographique en français et en polonais - Izert, Małgorzata (Neophilologica, 2018)
This article presents the analysis of nouns that act as indicators of large or very large undefined quantity. They have a structure in French DET N1 de and in Polish N1N2 (where N2 is used in genitive case). They are called ‘nominal quantifiers’ and are defined as formal indicators of the amplification of objects marked by nouns, which these quantifiers co-occur with. The set of nominal quantifiers being the subject of this analysis consists of 12 French nouns denoting meteorological phenomena or hydrographic forms and their equivalents in Polish. The semantic features of quantifiers and nouns that most often co-occur with them are analyzed. The semantic analysis allowed to distinguish two basic types of collocations with the use of these quantifiers: “prototype” collocations and figurative collocations, which in turn can be divided into several subtypes. Finally, there is presented a comparative analysis of the connectivity of these quantifiers in French and Polish languages.